Power, politics, and organizational change - Buchanan, David; Badham, Richard (Thousand Oaks : SAGE Publications, 2020)
"Organization politics can be seen as a game in which players compete for different kinds of territory such as status, power, and influence. In Power, Politics and Organizational Change, David Buchanan and Richard Badham ask: What's the relevance of politics to change and innovation? What kind of game is this? What, if any, are the rules? How is the game played? What ethical issues arise? Should one play this game to win, and if so, how? How can you develop political expertise? The third edition has been thoroughly updated and revised. This includes discussion of current trends heightening the importance of developing political will and skill in a post-truth era, the rise of 'new power', the role of 'BS busting', the power of storytelling, and the politics of speaking up"--
Keywords: politics; Organizational change